THE EFFECT OF PROBING PROMPTING LEARNING METHOD WITH PICTURE ON STUDENTS’ LEARNING MOTIVATION - Zainal Berlian; Nyayu Khodijah; Erie Agusta; Ayu Ariska Pratiwi (Al 'Ilmi : Jurnal Pendidikan MIPA, 2016)
Learning method Probing Prompting is a technique of learning by way of teachers presents a series of questions that are guided and dig so that there is a thought process that links the knowledge of each student and his experience with new knowledge being studied. This study aims to determine the effect of the use of learning method Probing Prompting with media images of students' learning motivation on science subjects in MTs Patra Mandiri Palembang academic year 2017/2018. This type of research is a quantitative research. The results showed that there was a positive influence on the use of the probingmethod prompting of student learning motivation, this can be seen from the results of t test ie t arithmetic 11.87 > t table 1,666 with significance level (α) = 0,05. It shows H a received and H 0 rejected, as well as based on comparison of mean scores and the percentage of student motivation indicates that the experimental class is superior to the control class. Keywords: education, learning, learning motivation